2010
DOI: 10.1177/0734242x10361511
|View full text |Cite
|
Sign up to set email alerts
|

Maturity and hygiene quality of composts and hygiene indicators in agricultural soil fertilised with municipal waste or manure compost

Abstract: Composts produced from municipal source separated biowaste (Biowaste), a mixture of biowaste and anaerobically digested sewage sludge (Biosludge) and cattle manure (Manure) were examined for their maturity and hygiene quality. The composts were applied to a potato crop in 2004 and to a barley nurse crop of forage ley in 2005 in a field experiment. Numbers of faecal coliforms, enterococci, clostridia and Salmonella in field soil were determined 2 weeks and 16 weeks after compost applications. Municipal compost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…The results showed that, after 21 days in the reactor, about 50% of the volatile solids were degraded, which corresponded to the values determined in similar experiments and in practice under real conditions [37,38]. The specific aeration during the entire duration of the experiment was 0.55 L/min/kg The duration of biological treatment at temperatures above 50 • C depends on the type of microorganisms in the mixture and the type of biowaste and can last from a few hours to several days [32,33]. For the substrate used, i.e., the biowaste sample, according to the European and Mediterranean Plant Protection Organization-EPPO (2008) and German "Ordinance on the Utilisation of Biowastes on Land used for Agricultural, Silvicultural and Horticultural Purposes-BioAbfV (1998) [34], it was necessary to prolong the thermophilic phase in a closed biowaste mixture and keep it at 55 • C for 14 days (consecutively) or at 60 • C for 7 days (consecutively) and at a moisture content of 40% and more to ensure hygienization.…”
Section: Aerobic Bioreactor Degradation Of Biowastesupporting
confidence: 82%
“…The results showed that, after 21 days in the reactor, about 50% of the volatile solids were degraded, which corresponded to the values determined in similar experiments and in practice under real conditions [37,38]. The specific aeration during the entire duration of the experiment was 0.55 L/min/kg The duration of biological treatment at temperatures above 50 • C depends on the type of microorganisms in the mixture and the type of biowaste and can last from a few hours to several days [32,33]. For the substrate used, i.e., the biowaste sample, according to the European and Mediterranean Plant Protection Organization-EPPO (2008) and German "Ordinance on the Utilisation of Biowastes on Land used for Agricultural, Silvicultural and Horticultural Purposes-BioAbfV (1998) [34], it was necessary to prolong the thermophilic phase in a closed biowaste mixture and keep it at 55 • C for 14 days (consecutively) or at 60 • C for 7 days (consecutively) and at a moisture content of 40% and more to ensure hygienization.…”
Section: Aerobic Bioreactor Degradation Of Biowastesupporting
confidence: 82%
“…Although at the end of the monitoring period, both the laboratory tests and the on-site tests indicated stability, this condition was indicated more rapidly (on day 86) in the laboratory tests, namely RI and the self-heating potential. This also indicates that the decisions based on only one quality test can be erroneous and it is necessary to simultaneously perform more tests to reach a decision (Komilis and Tziouvaras, 2009;Tontti et al, 2011).…”
Section: Comparisons Among Tests Of Stability and Maturitymentioning
confidence: 99%